Magnetite-Assisted Capture Affinity, Concentration Dependence, and Magnetic Extraction Rate of Bacillus cereus - Gouri Nilakshika Atapattu; Michelle Giltrap; Furong Tian (Microorganisms, 2025)
The interactions between magnetic nanoparticles (MNP) and bio-surfaces have impacted key industries such as food, biomedicine, water purification, and agriculture. Bacteria, with their diverse bio-surfaces, offer potential for such interactions. Yet, there is a paucity of research interpreting the dynamics behind bacteria–nanoparticle interactions. Advancing this knowledge could improve the industrial applications. Current research gaps include information about the magnetic nanoparticle-assisted concentration dependence of Bacillus cereus and determination of the rate of bacterial extraction by MNPs such as iron oxide nanoparticles (IONPs). Using magnetic IONPs as the choice of MNP, this study aimed to investigate in vitro the interactions between model bacteria and IONPs, leveraging the bacterial magnetising property. IONPs were synthesised by co-precipitation and characterised. Magnetic capture efficiency was reported for four model bacteria (Bacillus cereus, Escherichia coli, Staphylococcus aureus, and Salmonella typhimurium). The effect of particle concentration on the viability of Bacillus cereus and the rate of magnetic extraction of Bacillus cereus were evaluated. Bacillus cereus had the most robust interaction with IONP (90.34%). While the magnetic extraction was time-dependent, the average rate of magnetic extraction for Bacillus cereus was calculated as 3.617 CFU mL−1/min. Growth inhibition at 1.0, 2.0, and 4.0 mg mL−1 of IONP was significant. Magnetic capture results indicated that members of the Bacillus genus screened for plant growth-promoting traits may be suitable to combine with IONPs for future land application.